Negative infrared photocurrent response in layered WS2/reduced graphene oxide hybrids - Ratha, Satyajit; Simbeck, Adam J.; Late, Dattatray J.; Nayak, Saroj K.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
We report high performance IR photocurrent response of two-dimensional hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide (RGO). Comparative photocurrent response studies of WS2 nanosheets, RGO, and WS2/RGO hybrids were carried out by performing current-voltage (I-V) and time-dependent current measurements with a laser excitation source having a wavelength of 808 nm. The experimental investigations indicate that WS2/RGO hybrids show negative photocurrent response, whereas WS2 and RGO show positive photocurrent response. The negative photocurrent response of the WS2/RGO hybrids is explained using a band alignment diagram and attributed to a charge transfer mechanism between WS2 and RGO. This analysis is further corroborated by first-principles density functional calculations. The fabricated device based on WS2/RGO hybrids shows a photosensitivity R-lambda of about 6 AW(-1) and a quantum efficiency eta of similar to 924%, which demonstrates high sensitivity of the hybrid material towards IR detection. WS2/RGO hybrids are therefore promising candidates for potential applications in optoelectronic circuits and low cost, high performance, and reliable photodetectors. (C) 2014 AIP Publishing LLC.

Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Iron-carbon nanohybrid particles as environmentally benign electrode for supercapacitor - Ratha, Satyajit; Vernekar, Dnyanesh; Sivaneri, Kavin; Jagadeesan, Dinesh; Rout, Chandra Sekhar (Journal of Solid State Electrochemistry, 2017)
In this work, we report the synthesis and electrode applications of iron-carbon nanohybrid particles prepared by carbonization of a nanocomposite of FeOOH nanoneedles and melamine-formaldehyde resin. The chemical composition and microstructure of the material have been characterized using ICP-AES, FT-IR, XRD, FESEM, TEM and XPS. The supercapacitor properties of the MF-Fe-C are studied in detail. A thorough comparison of the supercapacitor performances of MF-Fe-C and bare MF-C has been carried out through detailed electrochemical characterisations employing both two and three-electrode techniques. The nanohybrid showed an enhanced energy density of 127.75 WhKg⁻¹, specific capacitance of ∼408 F g⁻¹ at 1 mVs⁻¹ scan rate, and excellent cyclic stability even after 1000 charge-discharge cycles, making it an intriguing material for high energy density supercapacitor devices.

Efficient bifunctional reactivity of K-doped CrO(OH) nanosheets: exploiting the combined role of Cr(iii) and surface -OH groups in tandem catalysis - Vernekar, Dnyanesh; Ratha, Satyajit; Rode, Chandrashekhar; Jagadeesan, Dinesh (Catalysis Science & Technology, 2019)
This work reports the bifunctional catalytic activity of layered K-doped alpha-CrO(OH). The combined action of the redox active Cr(III) and the surface hydroxyl groups was efficiently used to carry out 2-3 oxidation reactions in tandem followed by condensation/coupling reactions in one pot. Oxidation of benzyl alcohol followed by Knoevenagel condensation or coupling reactions forming C-C and C-N linkages in one pot is demonstrated. The catalyst has been characterized using XRD, IR, TGA, CO2-TPD, cyclic voltammetry, XPS and microscopic techniques to gain insight into the nature of active sites. The role of O- and O2- on the CrO(OH) catalyst in the bifunctional activity was studied using analytical techniques. Recyclability and leaching tests confirmed that K-alpha-CrO(OH) is a stable and environmentally safe catalyst.

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies